ANALISIS PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTIONS - Lia Witasari; Fuad Mas’ud; Ahyar Yuniawan (Jurnal Bisnis dan Ekonomi, 2011)
Turnover intentions in hospitality industry is a signal of the employee turnover in theindustry. The company shall give a serious attention because a high turnover within a companycan interrupt activities and productivities. Beside, turnover can also create instability anduncertainty of employee condition. According to the above, the researcher argues that it isnecessary to have a further examination about the relationship between job satisfaction andorganizational commitment, and turnover intentions in the hospitality industry. The deep theoryanalysis of variables affecting turnover intentions brings the researcher to develop a researchmodel consisting of three variables which are job satisfaction, organizational commitment, andturnover intentions as well as three research hypotheses. Data of job satisfaction, organizationalcommitment and turnover intentions is obtained through interviews using questionnaires to 142respondents who are employees of the Novotel Hotel. Then, data is analyzed using StructuralEquation Modeling (SEM) Technique of Analysis. The result of the three research hypotheses testusing SEM shows that job satisfaction has a positive and significant effect on organizationalcommitment, organizational commitment has a positive and significant effect on turnoverintentions, and job satisfaction statistically proven that it does not have any significant effect onturnover intentions. Based on that results, therefore the research questions are solved. Thatturnover intentions is affected by organizational commitment. Therefore, in order to push theturnover intentions in a low number, the management need to take efforts to improve theorganizational commitment of the employees.Key Words: job satisfaction, organizational commitment, turnover intention